1999
DOI: 10.1046/j.1525-1446.1999.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Health Promotion Lifestyle Among Three Ethnic Groups of Elderly Rural Women in Taiwan

Abstract: The purpose of this study was to examine the predictors of health promotion lifestyle (HPL) and examine the similarities and differences among three ethnic groups of elderly rural women in Taiwan. Pender's Health Promotion Model was used as the conceptual framework of this study. A convenience sample of 599 elderly rural women was recruited from three rural areas: Kao-Shu, San-Di-Men, and Ma-Chia. Ho-Lo, Hakka, and aboriginal people are the three main ethnic groups in these areas. Of the 599 elderly women, 391… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Exploring the elder participants' perceptions of health resulted in a functional definition of health, emphasizing the ability to do work and remain free from pain. This finding was consistent with Wang's (1999) study indicating that the majority of the Chinese aged, especially rural elders, defined health as physically functioning well and being free from pain. There is evidence that an individual's definition of health strongly influences health-promoting lifestyles (Pullen et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Exploring the elder participants' perceptions of health resulted in a functional definition of health, emphasizing the ability to do work and remain free from pain. This finding was consistent with Wang's (1999) study indicating that the majority of the Chinese aged, especially rural elders, defined health as physically functioning well and being free from pain. There is evidence that an individual's definition of health strongly influences health-promoting lifestyles (Pullen et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…We found that health‐promoting behaviors had no significant differences among multiethnic women in Taiwan. Wang's () study yielded the same result, in which no differences in health‐promoting lifestyles were found across three ethnic groups (Hokkien, Hakka, and Aborigine) of elderly females in Taiwan. Similarly, Bennett et al () found that among older adults, race/ethnicity was not related to utilizing mammogram screenings; however, race/ethnicity was related to older adults utilizing influenza vaccinations and dental checkups.…”
Section: Discussionmentioning
confidence: 70%
“…Health promoting behaviors have been shown to be positively related to age and education level 2,9,21,24) . However, Weitzel 11) found age to be negatively related to exercise and positively related to health responsibility and nutrition.…”
Section: Discussionmentioning
confidence: 99%